KEMAMPUAN PROFESIONAL GURU DAN KEMAMPUAN AKEDEMIK DOSEN DALAM UPAYA PENINGKATAN RELEVANSI DAN MUTU PENDIDIKAN NASIONAL - Soedijarto Soedijarto (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2006)
It is strongly believed that teacher’s professional competence and lecturer’s academic competence play significant role in improving the relevance and the quality of national education. This article therefore discusses teacher as a professional job and the reasons why the teachers must be professional in this 21st century, the program of teacher provision, lecturer as an academic human resource at higher education, and the financial implication of the teacher as professional job and the lecturers of higher education as scientific instructors. To end the article some notes on the problems discussed are presented in details.